PRODUCTION OF ACID AND ALKALI - NOMA YOSHIAKI; MAEHASHI TATSUYA (1995)
PURPOSE:To reuse caustic soda and sodium hydrogensulfide as a kraft liquor by recovering caustic soda, a carbonic acid gas and sulfuric acid from a smelt solution in a pulp production process. CONSTITUTION:A smelt solution 1 in a pulp production process is supplied to an electrodialyzer 1 alternately arranged with a cation exchange membrane and a monovalent anion selectively permeable membrane to recover a mixed aqueous solution 2 of sodium carbonate and sodium sulfate, and then, the mixed aqueous solution is fed to an electrodialyzer II using a highly porous membrane to produce caustic soda, sulfuric acid and a carbon dioxide gas.